Implementation of Patient Drug Prescription Services in Hospital Pharmacy Installations: Has It Been Managed Properly to Reduce Waiting Time? - Eka Kristia Ayu Astuti; Ayun Sriatmi; Farid Agushybana (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Abstract The hospital pharmacy installation plays an essential role in the hospital, where the hospital pharmacy installation manages the management and distribution of drugs. The achievement of quality indicators related to the waiting time for concoction and non-concoction drug services at the Outpatient Pharmacy Installation of X Kendal Hospital still needs to be consistent. Patients also complain about long waiting times. This study aims to determine whether the implementation of patient drug prescription services in the Hospital Outpatient Pharmacy Installation has been appropriately managed or needs improvement. This research is qualitative research with a phenomenological approach. Purposive sampling researchers selected the research subjects. The subjects in this study consisted of four primary informants and two triangulation informants. The results of the in-depth interviews found that during no initial check was made on the identity of the patient or the prescription received because due to the habit of piling up prescriptions, the dose given by the doctor was not correct. Hence, it had to be recalculated, the amount of drug stock in the system was not correct always the same as the available physical stock, lack of pharmaceutical staff during the drug preparation process, and there were medication errors in the drugs that had been prepared so that the staff had to re-prepare them, and errors in the drug delivery process due to staff negligence, causing longer waiting times for prescription services. Therefore, it was concluded that the implementation of prescription services at hospital X in Kendal district had not been managed optimally or appropriately. Hospitals still need to evaluate and improve the process of implementing prescription services to reduce waiting times. Keyword: Drug Prescription, Pharmacy Installation, Service